Teacher Instructional Leadership in Integrating Local Values at SMA Negeri 1 Gorontalo - Feronika Y. T, Alvita; Djafri, Novianty; Marhawati, Besse; Suking, Arifin (PPSDP International Journal of Education, 2025)
This study aims to investigate the instructional leadership practices of teachers at SMA Negeri 1 Gorontalo in integrating local values into the curriculum. It specifically focuses on identifying the forms of integrated local values, the leadership strategies employed by teachers, and the impact of this integration. This research employs a qualitative approach with a case study design. Data were gathered through in-depth observations, semi-structured interviews, and documentary analysis. The collected data were then processed using descriptive-qualitative analysis techniques. The findings reveal that: (1) Local values are integrated into learning through the multifaceted roles of teachers as educators, instructors, mentors, and classroom managers; (2) Key leadership strategies for integration involve establishing a clear vision and learning policies, implementing the structured “Every Day Five Goodness” program, and fostering community collaboration via the “Learning with Cultural Experts” initiative; (3) The integration has a significant positive impact, leading to enhanced teacher professionalism and the cultivation of strong, positive character in students. This study offers a novel perspective by shifting the focus from principal-led instructional leadership to teacher-led instructional leadership, specifically within the under-explored context of integrating local Gorontalo values to strengthen character education. The findings provide a practical framework for teachers and school administrators to systematically integrate local wisdom into national curricula. The identified strategies, such as the “Every Day Five Goodness” program, serve as a replicable model for other schools seeking to promote cultural preservation and character building. This research contributes to the fields of educational leadership and curriculum development by demonstrating how teachers can act as instructional leaders and agents of cultural preservation. It provides an evidence-based model for enhancing both teacher professionalism and student character outcomes through the deliberate integration of local values.